Protecting the identity and other rights of children born in 'foreign lands' to irregular migrant parents - Madamombe, Patience Ratidzo (Department of Public Law, 2015)
Children born in foreign territories to parents who are non-nationals are being deprived of the right to nationality, which in turn affects them from exercising other rights which are articulated in human rights instruments. When their births are not registered it means that they do not have birth certificates and in future they will be unable to acquire documents like identity documents and passports. Sometimes even if their births are registered, it is difficult for them to enjoy the other rights because national laws do not accommodate them. Even though all children's rights should be equally protected, this research will focus on children born to at least one parent who is an irregular migrant, and will analyse how this affects their access to the rights to education and health.